2020
DOI: 10.3390/agronomy10020160
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Rotation Patterns on Soil Organic Carbon in China’s Arid and Semi-Arid Regions

Abstract: The practice of crop rotation can significantly impact carbon sequestration potential. In exploring whether crop rotation has the potential to improve soil carbon sequestration in China’s Loess Plateau, soil organic carbon (SOC), soil water content (SWC), soil bulk density (SBD), and soil pH were compared across the 0–1.0 m soil profile, under four crop rotation patterns: lentil–wheat–maize, wheat–potato–lentil, wheat–maize–potato, and wheat–flax–pea. The lentil–wheat–maize and wheat–maize–potato rotations hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…For example, Alfalfa, as a primary rotation legume, is widely grown for animal feed for the fast-growing livestock industry (Wang et al, 2008) in the Loess Plateau of northwestern China, while also reducing soil erosion and improving soil fertility and quality (Jun et al, 2014). A recent study reported that the lentil-wheat-maize and maize-flax-pea rotations are the most suitable patterns to optimize simultaneous economic and ecological development of arid and semi-arid regions in China (Wei et al, 2020). Likewise, various other legume plants are planted with food and crops to improve soil fertility and characteristics (reviewed in Zeng et al (2016)).…”
Section: Management To Enhance Biomass Feedstock Productionmentioning
confidence: 99%
“…For example, Alfalfa, as a primary rotation legume, is widely grown for animal feed for the fast-growing livestock industry (Wang et al, 2008) in the Loess Plateau of northwestern China, while also reducing soil erosion and improving soil fertility and quality (Jun et al, 2014). A recent study reported that the lentil-wheat-maize and maize-flax-pea rotations are the most suitable patterns to optimize simultaneous economic and ecological development of arid and semi-arid regions in China (Wei et al, 2020). Likewise, various other legume plants are planted with food and crops to improve soil fertility and characteristics (reviewed in Zeng et al (2016)).…”
Section: Management To Enhance Biomass Feedstock Productionmentioning
confidence: 99%
“…Their results showed that oilseed rape performed well under moderate changes in soil temperature and rainfall regimes; hence, stable seed yields were observed, with no negative impact on seed nutrient quality. Wei et al [19] carried out a comparative study of rotation patterns on SOC in China's arid and semi-arid regions. They found that rotation practices of lentil-wheat-corn and corn-pea are the most appropriate models for optimizing simultaneous economic and ecological development, including water conservation and SOC sequestration.…”
Section: Effect Of Climate Change and Agricultural Practicesmentioning
confidence: 99%